Mechanical behavior, under four-point bending test, of compositions with soil, bio-char and charcoal (Research, Society and Development, 2020)
Soil stabilization for use in pavement sublayers has been established in Geotechnical En-gineering as an option for pavement construction. In this context, certain alternative materials stand out, such as coal and biochar, which are able to fulfill this function when added to the soil, being the object of study in the present research. These products originated from char-coal furnaces and biomass carbonization under low oxygen atmosphere. In the present study we evaluated the natural soil and compositions according to the four-point bending test, for simulating vehicle tire-loads on the pavement. For this purpose, we molded prismatic speci-mens with natural soil (NS) typical of the Amazon region, with natural soil-10% charcoal (SCH) and soil-10% biochar (SBC). It was verified that the soil-biochar mixture (SBC) pre-sented better results, culminating in higher values of complex modulus when compared to the natural soil (NS) and soil-charcoal mixtures (SCH). Regarding the phase angle parameter and the analyzed set (NS, SCH e SBC), values close to zero were observed. Therefore, this article presents the possibility of using alternative materials for executing road systems with better performance.